Minimally Invasive Spine Surgery A Practical Guide to Anatomy and Techniques - Ozgur, Burak; Benzel, Edward; Garfin, Steven; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Minimally Invasive Spine Surgery is a beautifully illustrated atlas describing the 18 most widely accepted minimally invasive procedures in spine surgery. Written by leaders in both neurologic and orthopedic spine surgery, this book offers the most up-to-date material and the broadest perspective on the subject. Procedures range from simple to complex and cover the cervical, thoracic and lumbar regions of the spine.
General Introduction and Principles of Minimally Invasive Spine Surgery -- Image-Guided Spinal Navigation: Principles and Clinical Applications -- Anterior Cervical Foraminotomy -- Posterior Cervical Foraminotomy and Laminectomy -- Posterior Cervical Instrumentation and Fusion -- Thoracoscopic Discectomy -- Thoracic and Lumbar Kyphoplasty -- Thoracoscopic Deformity Correction -- Paracoccygeal Transsacral Access to the Lumbosacral Junction for Interbody Fusion and Stabilization -- Facet Joint Anatomy and Approach for Denervation -- Facet Joint and Epidural Injections -- Discography and Endoscopic Lumbar Discectomy -- Discectomy and Laminectomy -- Combining Minimally Invasive Techniques for Treating Multilevel Disease as Well as Adult Degenerative Scoliosis -- Transforaminal Lumbar Interbody Fusion (TLIF) -- Lateral Approach for Anterior Lumbar Interbody Fusion (XLIF and DLIF) -- Anterior Lumbar Interbody Fusion (ALIF) -- Percutaneous Pedicle Screw Placement for Spinal Instrumentation -- Iliac Crest Bone Graft Harvest and Fusion Techniques -- Technologies for Use in Indirect Distraction Procedures.
Keywords: MEDICINE; ORTHOPEDICS; SURGERY; MEDICINE & PUBLIC HEALTH; SURGERY; ORTHOPEDICS